Community empowerment program to prevent Covid-19 transmission at Tahfidz Al-Qur'an Al Fath Islamic Boarding School, Pemalang - Fijianto, Dwi; Isyti'aroh, Isyti'aroh (Universitas Muhammadiyah Magelang, 2021)
Icor data from Pemalang Regency, Central Java, said that up to January 25, 2021, there were 3180 confirmed positive COVID-19 patients and 187 of them died. This community service activities are carried out to prevent the transmission of Covid-19 at the Tahfidz Al-Qur'an Al Fath Islamic Boarding School through community empowerment programs as a form of vigilance against infectious diseases caused by viruses. The activities carried out are providing health information through showing videos about Covid-19 and its transmission as well as prevention efforts with 3M. In addition, the community service team also provided training on how to wash hands in the correct 6 steps. The activity was attended by 31 participants consisting of caregivers and students of Islamic boarding schools. The results of the service revealed that participants' knowledge of Covid-19 prevention increased from 6.84 to 8.32.